Analysis of the religion element in nathaniel hawthorners young goodman brown short story - Sari, Juwita purnama; Triyogo, agus; Syaprizal (Lingustic, Literature and English Education, 2022)
ABSTRACT The objectives of this thesis was to describe the ReligionEelementsin Nathaniel Hawthorne’s Young Goodman Brown. The method applied in this research was descriptive qualitative method. This research used human instrument by herself. The data was analyzed by describing the elements of religion in short story. In collecting the data, the researcher read the short story and in analysing the data the researcher identifying religion element according to Rees theory. Based on the result of data analysis, the researcher found out data that: 1) God (s) and forces in the public square. The first element was belief in God2)sacred symbols (re) defining what is real were staff, meditation, ceremony, holy psalm, pulpit and Bible 3) sacred stories connecting past, present and future was good Cristians and honestmen,and 4) a community worshiping and acting together was Cristian congregation.In conlusion, the religion elements in Young Goodman Brown short story included belief, attitude and action in everyday life. Key word:Short Story, Religion Element